The tourist booklet as a genre of professional discourse: Interaction with the customer - Tatiana V. Dubrovskaya (Peoples' Friendship University of Russia (RUDN University), 2021)
This paper discusses touristic communication practices, specifically the tourist booklets as a genre of professional discourse. Using the framework that is informed by discourse analysis, multimodal discourse analysis, genre studies and professional discourse studies, the author views a tourist booklet as a complex multimodal genre and sets the goal to reveal how booklets construct interaction between professional agents and non-professional customers. Using a set of tourist (predominantly English language) booklets collected in 2005-2019 around the world, the author discovers professional agents seeking to strike a balance between their image as experts in tourism and the need to construct rapport with the customers. These goals are achieved through the employment of various strategies, which are implemented through a range of linguistic and visual techniques. The validity of the professional image relies on such discursive mechanisms as providing expert knowledge on the touristic objects and services, explicit indications of expertise, presentations of professional agents as law-abiding and formally recognised businesses, and references to socially important values. The meanings evoked by the linguistic resources are reinforced visually. To mitigate the asymmetry of statuses, rapport with the customers is developed by means of offering biographies and interviews with the company representatives, the demonstration of attention to the customer, the construction of common emotional space, and the conversational style strategy. The customer is also involved in cognitively entertaining or challenging activities. Thus, the study shows that professional-to-layperson communication is a multi-faceted phenomenon, whose complexity is predetermined by the combination of various intentions and multimodal resources that help implement these intentions discursively.